Unlearning and Transfer A Collaborative Autoethnographic Reflection on the Education Journey from Nepal to the United States - Khanal , Ananta; Bhusal, Purna Chandra (Journal of NELTA, 2025)
This article critically reflects on the educational journeys of two students and educators, from their experiences with school-level English education in Nepal to their first year of PhD studies in the United States. This reflection is informed by the methodological insights of collaborative autoethnography (CAE), as both authors share similar educational experiences. The theoretical concepts used in the reflection are unlearning and transfer. The authors‘ joint reflection identify es seven transitions involving unlearning and transferring. Based on these seven transitions, they derive seven key teaching-learning insights and propose a pedagogy grounded in a critical self-inquiry model. Therefore, the article explores innovative educational theories of unlearning and transfer in teaching and learning, while also opening avenues for further research.